The big heist : the real story of the Lufthansa heist, the Mafia, and murder - DeStefano, Anthony M. (Pinnacle Press, 2018)
One of the biggest scores in Mafia history, the Lufthansa Airlines heist of 1978 has become the stuff of Mafia legend--and a decades-long investigation that continues to this day. Pulitzer Prize-winning reporter Anthony DeStefano sheds new light on this legendary unsolved case using recent evidence from the 2015 trial of eighty-year-old Mafia don Vincent Asaro, who for the first time speaks out on his role in the fateful Lufthansa heist. This blistering you-are-there account takes you behind the headlines and inside the ranks of America's infamous crime families--with never-before-told stories, late-breaking news, and bombshell revelations: * New details on the heist's planning: who was involved, how they pulled it off, and what really happened to the almost $6 million in cash and jewels they stole from JFK Airport * Why suspected heist participant Vincent Asaro was found NOT GUILTY of all charges--racketeering, theft, and murder--even after being observed by the FBI for more than three decades * The shocking discovery of human bones in a Queens home belonging to a relative of Jimmy Burke, the homicidal Lucchese crime family associate who assembled the Lufthansa heist team--and masterminded the caper, then the biggest cash robbery in American history. * The eye-opening testimony of gangsters-turned-informants Salvatore Vitale and Gaspar Valenti--and what it reveals about the Mafia code of silence known as Omerta * The greed, betrayal, murder, and other frightening insights into the Bonanno and Lucchese crime families * Disturbing claims about how some members of the NYPD leaked information to mobster Jimmy Burke and may have helped hide evidence of a mob murder victim's demise An invaluable addition to any crime library, this is the most complete, thorough, and up-to-date account of the Lufthansa heist currently available. Pulitzer-Prize winner Anthony DeStefano draws from his years of experience reporting on the mob for New York Newsday--as well as his firsthand coverage of the Asaro indictment and attendence at the trial--to expose the all-too-human heart of organized crime in America. The Big Heist is thrilling, shocking, and impossible to put down.